Multilateral surface analysis of the CeB6 electron‐gun cathode used at SACLA XFEL. (18th October 2021) - Ohkochi, Takuo; Muro, Takayuki; Ikenaga, Eiji; Togawa, Kazuaki; Yasui, Akira; Kotsugi, Masato; Oura, Masaki; Tanaka, Hitoshi
Abstract : In this study, firstly the combination of low‐energy electron microscopy (LEEM), photoemission electron microscopy (PEEM), thermionic electron microscopy (TEEM) and synchrotron radiation was applied to the surface analysis of thermionic electron materials. The LEEM, PEEM and TEEM observations have been performed in a single cathode lens microscope, and the mechanism of age‐related degradation of the CeB6 cathodes which have been actually employed at SACLA X‐ray free‐electron laser (XFEL) facility was elucidated. Abstract : The CeB6 (001) single crystal used as a cathode in a low‐emittance electron gun and operated at the free‐electron laser facility SACLA was investigated using cathode lens electron microscopy combined with X‐ray spectroscopy at SPring‐8 synchrotron radiation facility. Multilateral analysis using thermionic emission electron microscopy, low‐energy electron microscopy, ultraviolet and X‐ray photoemission electron microscopy and hard X‐ray photoemission spectroscopy revealed that the thermionic electrons are emitted strongly and evenly from the CeB6 surface after pre‐activation treatment (annealing at 1500°C for >1 h) and that the thermionic emission intensity as well as elemental composition vary between the central area and the edge of the old CeB6 surface.